Implementation of Android Learning Media in the Subject of Machine Elements: Analysis of Needs and Readiness - Fajar Maulana (Journal of Hypermedia & Technology-Enhanced Learning, 2023)
Learning media plays a crucial role in supporting effective and interactive learning processes. In this digital era, using Android-based technology as a learning tool has become a primary focus in improving education quality. This article discusses the implementation of Android-based learning media in the Elements of Machines course context. The research aims to investigate the readiness and need for implementing Android-based Akidah Science learning media. The research method used is a survey, with research subjects consisting of second-semester students from the Vocational Automotive Technology Education Program at Universitas Lancang Kuning. Data was collected through questionnaire distribution, which was then analyzed descriptively. The research findings reveal several important discoveries. First, all students (100%) express interest in using Android-based learning media. Second, after a deeper understanding of the utilization of Android learning media, around 87.6% of students acknowledge the need for this media in the learning process. Third, the implementation of the ELR Aydin and Tasci model indicates that readiness to use Android learning media falls into “Ready” category, although some factors need slight improvement. The average ELR score reaches 3.73, exceeding the threshold of 3.4, indicating a level of readiness. However, it should be noted that the “Self-Improvement” aspect has a low ELR score of 3.24, indicating the need for improvement in this aspect. Overall, based on the research findings, it can be concluded that students show the need and readiness to use Android learning media in the context of the Elements of Machines course.